The Factors Of The Airport Experience That Affect Passenger Satisfaction And Behavioral Intentions At Yogyakarta International Airport - Zarra Isyana (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The airport has undergone a business transformation, from its previous focus solely on providing public facilities to becoming a multi-service provider that prioritizes the comfort of airline passengers by offering various activities, services, processes, and technologies that ultimately create an airport experience for passengers. Airport managers are under increasing pressure to provide desired Airport Experiences in the current competitive environment in order to draw in more travelers and airlines. This study will discuss the concept of airport experience by analyzing the influence of airport experience factors on passenger satisfaction and their intention to revisit, as well as spreading positive word of mouth. This study is planned to use a quantitative approach, with data obtained from primary sources using a questioner. Structure Equation Modelling method was performed to test the research hypothesis. The hypothesis will show if the factors of Airport Experience have positive effects on passenger satisfaction. Further, this passenger satisfaction is associated with their revisit intention and word of mouth. Previous research uses components of airport experience were measured from sociological, psychological, and services marketing perspectives and this research will add service quality dimension in a holistic approach. Based on the analysis about a thorough understanding of the most important aspects of the airport experience, the findings of this research expected to help airport management and marketers create strategies that will increase passengers' satisfaction, revisit intention, and positive word-of-mouth. This research will be held at Yogyakarta International Airport which is the new airport in Indonesia with a capacity of around 20 million passengers, and has not yet achieved the expected passenger target. So, this research is to provide valuable insights to airport management and marketers for developing better strategies to create better airport experience in order to increase passenger’s satisfaction and behavioral intention.